Mathematical Physics E-Module : Study of Students’ Perception Based on Gender - Astalini, Astalini; Darmaji, Darmaji; Kurniawan, Dwi Agus; Ramadhanti, Auliya (Journal of Education Technology, 2022)
Mathematics physics is often considered by students as a very difficult subject to learn, one of the causes that makes this happen is the lack of learning media that supports students. In addition, most of the existing media use foreign languages, so that in this case Indonesian language learning media is needed, namely the mathematical physics e-module on vector material which is then seen from student responses based on gender differences. This study aims to analyze students' perceptions of the mathematics physics e-module and to analyze students' perceptions based on gender differences in the mathematics physics e-module. This type of research is survey-based research with a quantitative approach. The population of this study was physics education students who contracted mathematical physics with a sample of 80 students. The instrument used in this study was a student perception questionnaire with 15 questions and an interview sheet with 10 questions. The data analysis technique used in this research is descriptive statistical analysis and inferential data analysis using t-test. The results showed that overall students had a positive perception with a perception value of 60% in the very good category and 40% in the good category, whereas when viewed from the gender difference, male students had a perception value of 76.6% in the very good category and 23, 3% in the good category, for female students 50% in the very good category and 50% in the good category. That is, students with gender differences have striking differences in perceptions. Student perceptions can be used as a determining factor in the selection of open materials. From the results, it can be seen that gender differences can help in assessing the products made so that they will support the learning process and increase student learning motivation.